2019
DOI: 10.1007/s40744-019-00183-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malignancies in Patients with Rheumatoid Arthritis Treated with Rituximab: Analyses of Global Postmarketing Safety Data and Long-Term Clinical Trial Data

Abstract: Introduction: Patients with rheumatoid arthritis (RA) are at an increased risk of developing malignancies, but it is unclear whether this increased risk is the result of disease pathobiology or immunosuppressant treatments for RA. This analysis evaluated the potential risk of malignancy in patients with RA treated with rituximab (MabThera Ò /Rituxan Ò) a CD20? B-cell depleting agent manufactured by F. Hoffmann-La Roche Ltd. Methods: Malignancy rates were obtained from the rituximab global company safety databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In other pathologies, such as neuromyelitis optica spectrum, monitoring of CD19+ and CD28+ was performed every 3 months, in order to perform infusion only if these lymphocytes were detectable [30]. This method could lead to more individualized administration of rituximab with similar efficacy and less risk of AEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other pathologies, such as neuromyelitis optica spectrum, monitoring of CD19+ and CD28+ was performed every 3 months, in order to perform infusion only if these lymphocytes were detectable [30]. This method could lead to more individualized administration of rituximab with similar efficacy and less risk of AEs.…”
Section: Discussionmentioning
confidence: 99%
“…There is no augmentation of risk of neoplasia with exposition to rituximab. The risk is estimated at 4.2 events per 1000 treated patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…[29] Other bDMARDs have been much less studied, but the data from meta-analyses and long-term extension studies showed no increased overall malignancy risk for rituximab, abatacept, and tocilizumab. [21,25,[30][31][32][33] Recently, other studies suggested that abatacept use is associated with a slight increase in skin cancer risk, both NMSC [34] and MSC. [6] In our cohort, the IR of malignancy was 3.47 per 1000 p-y, with a higher value was found in the RA subgroup (5.2 per 1000 p-y).…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of three clinical trials (DANCER, REFLEX and IMAGE) has demonstrated that RTX were comparable to placebo and MTX in terms of serious infections rate [ 96 , 133 ]. No increased risk of malignancies in patients treated for RA with rituximab was observed [ 134 ]. Yet, a major concern was raised on risk of reactivation of hepatitis B-virus (HBV) infection during RTX treatment compared to etanercept [ 133 ].…”
Section: Bdmards Based On Cell-targeted Therapymentioning
confidence: 99%